EKSISTENSI PENDIDIKAN ISLAM UNTUK MENJAWAB TANTANGAN PERUBAHAN DUNIA PENDIDIKAN DI ERA MILENIAL - Syahroni, Imam; Diantoro, Fery; Wicaksono, Trio Arreza; Hermawati, Kiki Ayu; Nisak, Ulin Nuha Ngarifatun; Widodo, Wahyu (IAIIG Cilacap, 2020)
This article tried directing Islamic education can open with industri revolution 4.0 and with result that Islamic education and Islamic education does not look traditional and is capable to education neo-modernis. An education that balance between al-Quran, as-Sunnah, ulama holy books and technology so that Islamic education not experience disharmony between technology with education and Islamic education will be a central education if can to process that materials. So that Islamic education will be result a smart student in knowledge and technology